HUBUNGAN TINGKAT PENGETAHUAN IBU PUS TENTANG KANKER SERVIKS DENGAN PEMERIKSAAN IVA - Masyuji Rale; Kristiani Murti Kisid; Fidiya Rizka (Jurnal Midwifery Update (MU), 2022)
Introduction: According to WHO there are 530,000 new cases representing 7.5% of all cancer deaths that occur in women, and every year thousands of women die because of cervical cancer. The main strategy to reduce mortality from cervical cancer is to perform early detection. Objectif: The purpose of this study was to determine the relationship between the level of knowledge on women of childbearing age (PUS) about cervical cancer with IVA checkup in Seteluk Tengah Village, West Sumbawa Regency.Method: This study uses an analytical survey method with a cross sectional approach with the research instrument, namely a questionnaire. The study population was 789. The sample in this study was PUS women aged 15-49 years with technique cluster random sampling total of 100 samples. Data anlysis using chi-square statistical test with SPSS.Result: The results showed that the majority of respondents with high school education status were 36 people (36%) and at 17 respondents were college graduates (17%), the lowest age of respondents was 21 years and the highest was 49 years, as many as 58 respondents (58%) did IVA checkup, and 42 respondents (42%) did not do IVA checkup.  Respondents with good knowledge as many as 18 people (18%) did not do IVA and 34 people (34%) did IVA checkup. It can be concluded that there is no significant relationship between the level of knowledge on women childbearing age (PUS) about cervical cancer and the IVA checkup with the results of the chi-square test  p-value 0.297 (> 0,05).Conclusion: Based on these results, it is recommended that health workers can make health promotion efforts in increasing knowledge about early detection of cervical cancer and to women who are in childbearing age (PUS) are expected to continue to try to obtain information about cervical cancer and undergo IVA checkup as an effort to detect cervical cancer early.